A spectroscopic study of uranyl speciation in chloride-bearing solutions at temperatures up to 250 °C. (1st February 2018) - Migdisov, A.A.; Boukhalfa, H.; Timofeev, A.; Runde, W.; Roback, R.; Williams-Jones, A.E.
Abstract: The speciation of U in NaCl-bearing solutions at temperatures up to 250 °C and concentrations of NaCl up to 1.5 m has been investigated using an in situ spectroscopic technique. The recorded spectra permit us to identify the species present in the solutions as UO2 2+, UO2 Cl +, and UO2 Cl2 °. UO2 Cl3 − is also likely present at high temperatures and NaCl concentrations, but concentrations of this species are insufficient for derivation of the formation constants. No evidence was found for species of higher ligand (Cl − ) number. Thermodynamic stability constants derived for these species show fair agreement with published data for 25 °C, but differ significantly from those predicted by an earlier high-temperature study (Dargent et al., 2013), which suggested that UO2 Cl4 2− and UO2 Cl5 3− contribute significantly to the mass balance of uranyl chloride complexes, especially at high temperature. In contrast, our data suggest that the main uranyl-chloride complex present in aqueous solutions at T > 150 °C and concentrations of NaCl relevant to natural hydrothermal systems is UO2 Cl2 °. The values of the logarithms of thermodynamic formation constants (β) for the reaction UO2 2+ + Cl − = UO2 Cl + are 0.02, 0.25, 0.55, 1.09, 1.59, and 2.28 derived at 25, 50, 100, 150, 200, and 250 °C, respectively. For the reaction UO2 2+ + 2Cl − = UO2 Cl2 ° the values of log β derived at these temperatures are 0.4, 0.58, 0.74, 1.44, 2.18, and 3.42. Values of the formation constant estimated for uranyl-chloride species predict the high concentrations of U observed by Richard et al. (2011) in fluid inclusions of the giant McArthur River unconformity-type uranium deposit.